GARDEN CITY’: THE SUITABILITY OF ITS PRINCIPLES AS A MODEL TO THE CONTEMPORARY PLANNING - Evalina Evalina; Husnus Sawab (Universitas Muhammadiyah Jakarta, 2011)
ABSTRACT. Garden City is an urban planning concept that adopted from of Ebenezer Howard who developed the idea of garden cities as a way towards a better and brighter civilization. This article discuss the Garden City concept as associated to planning evolution and describes the later changes in approach to planning better cities in current circumstances. Based on arguments from some experts and evidence derived from practice, Garden City is the novel idea that has a unique presentation because of its simplicity and range of details which consist of three main elements including decentralization, garden and city or in simple terms are location, physical design and community ownership. These days, while in some extent the Garden City idea is still attractive especially in terms of the idea of green design and social city model, the appropriateness of the Garden City idea to contemporary planning seems invalid. The Garden City concepts such as decentralization, low density, self-containment communities, new settlements and proportion of population to land are not anymore fit with current situation which is urban population growth rapidly imbalance with land availability. Urban concept today tends to consider environmental approach in order to gain sustainable goals such as ‘compact city’ concept in planning the better city. The Garden City has a valuable contribution to evolution of urban and regional planning approach, but it is not entirely relevant to the contemporary planning approach. Keywords: Garden City, Contemporary Planning ABSTRAK. Garden city adalah salah satu konsep perencanaan perkotaan yang diadopsi dari karya Ebenezer Howard yang mengembangkan ide ‘kota taman’ sebagai langkah menuju sebuah peradaban yang lebih baik. Tulisan ini mendiskusikan konsep Garden City terkait perkembangan perencanaan kota dan menjelaskan perubahan terkini dalam pendekatan perencanaan kota yang lebih baik. Berdasarkan pendapat beberapa ahli dan hasil penerapan yang pernah dilakukan, Garden city adalah sebuah konsep awal yang memiliki sebuah keunikan dikarenakan kesederhanaannya dan detil yang beragam. Konsep Garden city terdiri dari 3 (tiga) elemen utama, yaitu: desentralisasi, garden dan city atau dengan istilah lain adalah lokasi, desain fisik, dan kepemililkan masyarakat (community ownership). Konsep Garden City sampai saat ini cukup mendapat perhatian terkait dengan konsep green design dan social city model. Tetapi, beberapa konsep lainnya dari Garden City seperti, disentralisasi, tingkat kepadatan yang rendah, masyarakat mandiri, pemukiman baru, dan proporsi jumlah penduduk terhadap lahan tidak sesuai dengan situasi saat ini dimana pertumbuhan penduduk kota yang sangat cepat tidak seimbang dengan ketersediaan lahan. Konsep perkotaan masa kini cenderung mempertimbangkan pendekatan lingkungan untuk mencapai sustainable goals seperti, konsep compact city dalam merencanakan kota yang lebih baik. Konsep Garden City memiliki kontribusi yang bernilai terhadap perkembangan pendekatan perencanaan kota dan wilayah, tetapi tidak secara keseluruhannya relevan pada pendekatan perencanaan masa kini. Keywords: Kota Taman, Perencanaan masa kini